The impact of a comprehensive strategy on HIV treatment continuum in a highly endemic area of China: an interrupted time series analysis - Ruiying Liang; Fangfang Chen; Houlin Tang; Ju Wang; Decai Zhao; Junjie Wang; Jiejun Yu; Jian Li; Jun Yan; Zhongfu Liu (BMC Infectious Diseases)
Abstract Background A comprehensive strategy encompassing universal testing and strengthened treatment was promoted to address the severe HIV epidemic in Liangshan. This study aimed to assess the impact of this strategy on HIV treatment continuum. Methods Interrupted time series (ITS) analysis was utilized to evaluate the impact of a comprehensive strategy on HIV treatment outcomes in Liangshan from 2014 to 2021 utilizing data from China's HIV/AIDS Comprehensive Response Information Management System (CRIMS). Poisson or quasi-Poisson segmented regression models were applied to estimate the trends and immediate changes in key outcomes, including the proportion of 30-day antiretroviral therapy (ART) initiation, the proportion of 6-month follow-up, and the proportion of viral suppression, following the strategy's implementation in January 2018. The analysis was stratified by sex, age, transmission route, and region, with areas classified as key areas and non-key areas based on an HIV prevalence threshold of 1%. Results A total of 37,888 people living with HIV (PLHIV) were identified during the study period, with an increase in diagnoses following comprehensive strategy implementation. Most cases involved males, aged 15–34 years, residents of key areas, and individuals infected through heterosexual transmission. There was a significant increase of 2.50-fold in 30-day ART initiation (incidence rate ratio [IRR] 2.501, 95% CI: 1.694–3.694), 34.0% in 6-month follow-up (1.340, 95% CI: 1.234–1.456), and 17.7% in viral suppression (1.177, 95% CI: 1.068–1.296) in the first month of comprehensive strategy implementation. Over time, all three indicators displayed an upward trend, and by December 2021, their predicted values significantly increased, exceeding the expected levels by 60.3% (IRR 1.603, 95% CI: 1.108–2.318), 62.9% (1.629, 95% CI: 1.430–1.855), and 50.6% (1.506, 95% CI: 1.223–1.855), respectively. Subgroup analysis revealed that while the strategy's effects on these outcomes were generally consistent, the magnitude of improvement varied. Residents of key areas exhibited more significant increases in 30-day ART initiation, while residents of non-key areas, particularly those aged ≥ 60 years, displayed smaller increases in the proportion of 6-month follow-up, and no significant change in the proportion of viral suppression, with a slightly lower average. Conclusions The implementation of a comprehensive strategy substantially improved timely ART initiation, follow-up care after ART and viral suppression for PLHIV in Liangshan, with consistent enhancements across various subpopulations. It is imperative to strengthen comprehensive strategy in non-key areas of Liangshan, and to promote these strategies in other similar regions in order to enhance health benefits for patients.